2015
DOI: 10.1097/ta.0000000000000518
|View full text |Cite
|
Sign up to set email alerts
|

Lung protective ventilation (ARDSNet) versus airway pressure release ventilation

Abstract: Background Concomitant lung/brain traumatic injury, results in significant morbidity and mortality. Lung protective ventilation (ARDSNet) has become the standard for managing acute respiratory distress syndrome (ARDS); however, the resulting permissive hypercapnea may compound traumatic brain injury (TBI). Airway pressure release ventilation (APRV) offers an alternative strategy for management of this patient population. APRV was hypothesized to retard the progression of acute lung/brain injury to a greater de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Similar to the F-APRV studies, P-APRV either resulted in improved outcomes or no change as compared with CPPV and in none of the studies was APRV shown to be harmful. Unlike the F-APRV studies that were mainly crossover studies, all of the P-APRV animal studies were randomized prospective cohort trials that compare non-protective CPPV or low tidal volume (LTV) with APRV [ 5 , 49 , 52 , 54 , 55 , 57 , 61 , 62 ]. P-APRV was shown to reduce heterogeneity and both alveolar and alveolar duct micro-strain (i.e., change in alveolar size with applied stress) [ 54 56 ] suggesting a mechanism for the improvement in the efficacy experiments (Table 3 ) [ 5 , 49 , 57 , 61 , 62 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the F-APRV studies, P-APRV either resulted in improved outcomes or no change as compared with CPPV and in none of the studies was APRV shown to be harmful. Unlike the F-APRV studies that were mainly crossover studies, all of the P-APRV animal studies were randomized prospective cohort trials that compare non-protective CPPV or low tidal volume (LTV) with APRV [ 5 , 49 , 52 , 54 , 55 , 57 , 61 , 62 ]. P-APRV was shown to reduce heterogeneity and both alveolar and alveolar duct micro-strain (i.e., change in alveolar size with applied stress) [ 54 56 ] suggesting a mechanism for the improvement in the efficacy experiments (Table 3 ) [ 5 , 49 , 57 , 61 , 62 ].…”
Section: Reviewmentioning
confidence: 99%
“…In prospective outcome animal experiments, P-APRV resulted in an increase in oxygenation along with a decrease in histopathologic injury as compared with CPPV and LTV ventilation strategies [ 5 , 52 , 57 , 61 , 62 ]. Several studies showed that P-APRV resulted in an increase in surfactant protein concentration [ 5 , 57 , 62 ], while two showed a reduction of inflammatory markers (Table 2 ) [ 49 , 57 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of E L was induced by slowly instillation of 0.1 mol/L hydrochloride (4 mL/kg) down the endotracheal tube via a thin suction catheter placed at the level of the carina. This method has been previously reported as creating an animal model with ARDS-like lung injury including lung inflammation, edema, hemorrhage, and variable lung region aeration [ 25 , 26 ]. One hour following hydrochloride administration the model was validated by achieving a pulse oxygen saturation ≤ 90%.…”
Section: Methodsmentioning
confidence: 99%
“…IH was induced by inflating the intracranial balloon with saline at a rate of 0.5 mL/min until the ICP was constant between 30 and 40 cm H 2 O for > 30 min [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%